Global groundwater?: issues and solutions - Giordano, Mark (Annual Reviews, 2009)
Groundwater plays a major, if often unrecognized, role in both hydrologic and human systems. The majority of the world's drinking water probably comes from groundwater, and in the last half century, there has been an amazing, if largely ignored, boom in agricultural groundwater use that has provided improved livelihoods and food security to billions of farmers and consumers. However, increased use of groundwater has also created problems, and there are fears?sometimes challenged? that the boom may soon turn to bust. This article reviews the recent literature on the geographic and temporal dimensions of groundwater use and the range of technological and institutional approaches which have been applied in attempts at its management. It then examines the key reasons the resource has proven so difficult to manage and concludes that, in many cases, the most promising solutions may lie outside the groundwater sector and within a broader approach to resource systems.